Development of area-based yield index insurance for rice based on satellite data - Raviz, Jeny; Gutierrez, Mary Anne; Dela Cruz, Israel; Alosnos, Elmer; Garcia, Cornelia; Castillo, Rowena; Hellin, Jon; Laborte, Alice (International Rice Research Institute, 2024)
Rice farming in the Philippines is highly vulnerable to climate risks, particularly affecting smallholder farmers. Traditional indemnity-based crop insurance provides some level of protection; however, it often falls short due to slow claims processing, subjective damage assessments, and inadequate coverage. To address these gaps, the Philippine Crop Insurance Corporation (PCIC), the Philippine Rice Research Institute (PhilRice), and the International Rice Research Institute (IRRI) have partnered to develop an innovative area-based yield (ARBY) index insurance using satellite data. ARBY relies on historical average yields for specific geographic areas to determine payouts when crop losses occur. It was tested in six municipalities during the 2023-2024 dry season, resulting in payouts for two municipalities where yields fell below the trigger yield.